2018
DOI: 10.2147/ceor.s146095
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic impact of the 21-gene recurrence score assay in adjuvant therapy decision making in patients with early-stage breast cancer: pooled analysis in 4 Basque Country university hospitals

Abstract: PurposeThe 21-gene recurrence score (RS) is a genomic test developed as a prognostic and predictive tool to improve the treatment decision making in cases of estrogen receptor-positive and human epidermal growth factor receptor 2-negative early-stage breast cancer. This study examined the clinical and economic impact of its use in 4 Basque Country university hospitals.MethodsTaking into consideration the RS result, we recorded the recommended initial systemic adjuvant therapy (endocrine therapy with or without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Studies in the US ( n = 19; 36%) [ 19 37 ] and Canada ( n = 9; 17%) [ 38 46 ] made up the majority of our identified studies ( n = 28; 53%), followed collectively by the Western European countries ( n = 22; 42%). In Western Europe, most studies were in Italy ( n = 5; 9%) [ 47 – 51 ], then Spain ( n = 4; 8%) [ 52 55 ], France ( n = 4; 8%) [ 56 59 ], Netherlands ( n = 3; 6%) [ 60 62 ], UK ( n = 3; 6%) [ 63 65 ], Sweden ( n = 2; 4%) [ 66 , 67 ], and Germany ( n = 1; 2%) [ 68 ]. Three (6%) studies were in Australia [ 69 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies in the US ( n = 19; 36%) [ 19 37 ] and Canada ( n = 9; 17%) [ 38 46 ] made up the majority of our identified studies ( n = 28; 53%), followed collectively by the Western European countries ( n = 22; 42%). In Western Europe, most studies were in Italy ( n = 5; 9%) [ 47 – 51 ], then Spain ( n = 4; 8%) [ 52 55 ], France ( n = 4; 8%) [ 56 59 ], Netherlands ( n = 3; 6%) [ 60 62 ], UK ( n = 3; 6%) [ 63 65 ], Sweden ( n = 2; 4%) [ 66 , 67 ], and Germany ( n = 1; 2%) [ 68 ]. Three (6%) studies were in Australia [ 69 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given the results in the present review, it may be surprising that the guidelines update in 2017 [ 55 ], but not in 2019 [ 17 ], emphasised that node-positive patients should be informed of the potential benefits from chemotherapy. Indeed, an internationally used “objective” test result may have a large impact on chemotherapy decision making, which is illustrated by the fact that several studies have been performed in patients with intermediate clinical risk of recurrence, in which the chemotherapy decision was based solely on the results of the gene expression assay [ 26 , 45 , 56 ]. Conversely, our results suggest that many oncologists and patients take clinical parameters into account, also when the gene expression assay shows a low/intermediate risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…It may be argued that the introduction of gene expression assays will reduce the provision of chemotherapy, thereby reducing the costs to justify a potential worse patient outcome. However, chemotherapy decision making studies in the relevant patient group have reported both increased [44][45][46][47] and decreased [48][49][50][51] administration of chemotherapy when gene expression assay results are provided, and none of these studies had a randomised design. Also, from an ethical perspective, withholding an established treatment may be more problematic than introducing a new one.…”
Section: Discussionmentioning
confidence: 99%
“…Although choice of adjuvant treatments in treatment guidelines can differ among countries, the association between using molecular profiling assays and a change in treatment decisions and an overall reduction in chemotherapy use is consistent 22 , 121 , 122 , 123 . By avoiding chemotherapy treatments, improvements in patientsʼ quality of life and overall cost savings for health systems can be achieved, despite the negative economic impact in the short term caused by the cost of the molecular tests 124 , 125 .…”
Section: Reviewmentioning
confidence: 99%